2013
DOI: 10.1371/journal.pone.0069597
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Radiocarbon, Stable Isotopes and DNA in Teeth to Facilitate Identification of Unknown Decedents

Abstract: The characterization of unidentified bodies or suspected human remains is a frequent and important task for forensic investigators. However, any identification method requires clues to the person’s identity to allow for comparisons with missing persons. If such clues are lacking, information about the year of birth, sex and geographic origin of the victim, is particularly helpful to aid in the identification casework and limit the search for possible matches. We present here results of stable isotope analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…Atmospheric 14 C (as 14 CO 2 ) enters the terrestrial biosphere by photosynthesis; 14 C is subsequently incorporated into herbivore tissues as the animals ingest plants for food. The bomb- 14 C signal has been used in human forensic studies (17)(18)(19)(20)(21) and has also been used previously to date ivory and other animal tissues including hair, horn, and tooth enamel (22)(23)(24)(25). Prior work on 14 C dating of ivory has used the atmospheric 14 C/ 12 C historical record to determine the calibrated age of samples.…”
Section: Resultsmentioning
confidence: 99%
“…Atmospheric 14 C (as 14 CO 2 ) enters the terrestrial biosphere by photosynthesis; 14 C is subsequently incorporated into herbivore tissues as the animals ingest plants for food. The bomb- 14 C signal has been used in human forensic studies (17)(18)(19)(20)(21) and has also been used previously to date ivory and other animal tissues including hair, horn, and tooth enamel (22)(23)(24)(25). Prior work on 14 C dating of ivory has used the atmospheric 14 C/ 12 C historical record to determine the calibrated age of samples.…”
Section: Resultsmentioning
confidence: 99%
“…; Alkass et al . ). Using racemization, it has been demonstrated that the half‐life of horse tendon is around 200 years in high strain, injury‐prone superficial digital flexor tendon, and far less (∼34 years) in low strain and rarely injured common digital extensor tendon (Thorpe et al .…”
Section: Introductionmentioning
confidence: 97%
“…The average F 14 C of the soluble fraction of control Bt ken spores was 1.078 ± 0.032 (1 SD) for a chronological uncertainty of ± 6 years. This is more variability than typically seen in bomb pulse dating [2227,31,33,37] and was attributed to initial use of a shared lyophilizer to dry control spore preparations. Pump oil and solvents can contaminate samples with 14 C-free carbon, causing depressions in F 14 C by adding carbon mass that is devoid of 14 C. As noted, some spore samples were not miscible in initial extraction components indicating significant surface contamination, however, in subsequent steps slurries were obtained.…”
Section: 0 Resultsmentioning
confidence: 99%
“…Additionally, the 14 C bomb-pulse has been used for forensic dating organic material and teeth of recent origin [10,2231]. Although bomb pulse dating was not developed using microorganisms, the same general principles of 14 C sample definition and analysis that apply to higher-order organisms also apply to heterotrophic bacteria.…”
Section: 0 Introductionmentioning
confidence: 99%